2004
DOI: 10.1051/0004-6361:20040222
|View full text |Cite
|
Sign up to set email alerts
|

New period-luminosity and period-color relations of classical Cepheids

Abstract: Abstract. Photometric data for 593 Cepheids in the LMC, measured by Udalski et al. in the OGLE survey, augmented by 97 longer period Cepheids from other sources, are analyzed for the period-color (P-C) and period-luminosity (P-L) relations, and for the variations of amplitude, light curve shape, and period across the instability strip at constant absolute magnitude. Both the P-C and P-L relations have different slopes for periods smaller and larger than 10 days. The break at 10 days is also seen in the period-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
268
4
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(298 citation statements)
references
References 87 publications
(141 reference statements)
25
268
4
1
Order By: Relevance
“…Considering the observations of Cepheids in the Galaxy and the Magellanic Clouds (Tamman et al 2003;Sandage et al 2004Sandage et al , 2009, we show that the observed instability strip is narrower than the theoretical one, and that the slope of the lower boundary of observed stars coincides with the slope of the faint envelope connecting each of the loops of the theoretical tracks for the chemical composition of the MCs. Because of the small number of Cepheids in open clusters and associations of the Milky Way, we cannot draw the lower boundary of the observed strip as we did for the MCs, but in this case, the loops of the theoretical models can also indicate the location of MW Cepheids in the HR-diagram.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…Considering the observations of Cepheids in the Galaxy and the Magellanic Clouds (Tamman et al 2003;Sandage et al 2004Sandage et al , 2009, we show that the observed instability strip is narrower than the theoretical one, and that the slope of the lower boundary of observed stars coincides with the slope of the faint envelope connecting each of the loops of the theoretical tracks for the chemical composition of the MCs. Because of the small number of Cepheids in open clusters and associations of the Milky Way, we cannot draw the lower boundary of the observed strip as we did for the MCs, but in this case, the loops of the theoretical models can also indicate the location of MW Cepheids in the HR-diagram.…”
Section: Discussionsupporting
confidence: 46%
“…The blue and red dotted lines correspond to the blue and red boundaries of the instability strip, such that the strip contains ∼90% of the Cepheids (Fig. 8 of Sandage et al 2004). The blue and red long-dashed lines are the boundaries of the theoretical strip as represented by the formulae of Caputo et al (2004) for the appropriate chemical composition.…”
Section: Cepheidsmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal set exhibits less scatter (rms = 0.21 mag) around the relation M V = (−3.08 ± 0.50) log P + (−0.94 ± 0.42) mag, with considerable uncertainty in both the zero point and the slope. We note that our result is in near exact agreement with the PLR in Sandage et al (2004), although nearly all of the PLRs shown in Fig. 1 agree with our results to within their uncertainties.…”
Section: The Plr Calibrationsupporting
confidence: 88%
“…We illustrate this fact in Fig. 1, which shows PLRs based on different methods, including absolute and relative trigonometric parallaxes, BaadeBecker-Wesselink-type methods, as well as the calibration by Sandage et al (2004) which is partially based on Cepheids in Galactic open clusters. In light of such discrepancies, we deem that a self-consistent analysis of membership for CCs is warranted, and here we present a calibration obtained from the preliminary results of our mostly literaturebased, eight-dimensional, self-consistent all-sky census of classical Cepheids in Galactic open clusters.…”
Section: Introductionmentioning
confidence: 96%